The corporate conundrum: how to blend people and process to improve firm performance - Rathakrishnan, Thanuja; Siew, Imm Ng; Jo, Ahn Ho; Zawawi, Dahlia (Fundacao Escola de Comercio Alvares Penteado (F E C A P), 2021)
Purpose – One of the challenges in the business world is maximising effectiveness and firm performance. This study proposes that the right blend of people (with openness to change and self-transcendence values) and process (effectuation) would result in innovative behaviour and firm performance. Theoretical framework – The effectuation process has been found to be useful in promoting innovativeness, especially among small firms whose resources are scarce. This relationship is also true in large firms, although these have more resources and operate in a relatively stable environment. Design/methodology/approach – Using a snowball sampling approach, a total of 206 completed questionnaires were collected online from employees involved in decision making and innovative work processes in multinational companies in Selangor, Malaysia. PLS-SEM was used to analyse the data. Findings – The right people (who are open to change or self-transcendent) blended with the right process (effectuation) were found to positively predict innovative behaviour and firm performance. Effectuation and innovative behaviour also mediated the relationships between individual values and firm performance, suggesting that people and process should coexist to enhance firm performance. Research Practical & Social implications – Effectuation is scarcely practised in large firms. Therefore, we suggest that large firms encourage the use of effectuation through training. As the practice is better received among individuals who are open to change and self-transcendent, these values could also be used as hiring criteria. Originality/value – This study contributes to the literature by analysing the roles of people and process in optimising firm performance, and identifying effectuation and innovative behaviour as mechanisms that link individual values to firm performance.